Bank Efficiency and Competition in Low-Income Countries : The Case of Uganda - Hauner, David (IMF Working Papers; Working Paper, 2005)
There is a concern that the state-dominated, inefficient, and fragile banking systems in many low-income countries, especially in sub-Saharan Africa, are a major hindrance to economic growth. This paper systematically analyzes the impact of the far-reaching banking sector reforms undertaken in Uganda to improve competition and efficiency. Using models that have been previously used only in industrial countries, we find that the level of competition has increased significantly and has been associated with a rise in efficiency. Moreover, on average, larger banks and foreign-owned banks have become more efficient, while smaller banks have become less efficient in the face of increased competitive pressures.